Prevalence of Musculoskeletal Disorders among Pregnant Women: Cross-Sectional Study - Hafsah Gul Khattak, Hafsah Arshad, Kinza Anwar, Sidra Hanif, Nida Kiani, Bushra Sultana (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To identify the prevalence of most common musculoskeletal disorders in pregnant women according to trimester. Method: A cross-sectional study was conducted from September 2019 to February 2020. The study was conducted after taking approval from the study setting and by the research ethics committee. The data was collected from the Family health hospital Islamabad. Data was raised through non-probability convenient sampling technique. Pregnant females with the age group of 20 to 40 years were included in the study. Those who had a chronic musculoskeletal conditions and previous history of orthopedic surgery were excluded. Data was collected after taking written informed consent. Data was collected using semi structured questionnaire which included demographic information, questions related to pregnancy and questions about musculoskeletal problems during pregnancy. Results: The mean age of 385 participants was 27±4.76. Low back pain (38.7%) was the most prevalent musculoskeletal disorder among pregnant women. In first trimester, low back pain and muscle cramps were found to be (33.3%) and (20%). In second trimester the most frequent problem was low back pain (37.6%), leg muscle cramps (17.6%), pedal edema (10.3%) and carpel tunnel syndrome (9.1%) respectively. Whereas, in third trimester 40.5% mentioned pain in low back, 16.3% leg muscle cramps, 10% pedal edema, 8.4% had reported carpal tunnel syndrome. Conclusion: Low back pain, leg muscle cramps and pedal edema were the most experienced musculoskeletal problems in pregnant woman.